The Role of Tafsir in Supporting Religious Moderation Programs - Syahda Naurah; Ainur Rhain; Yeti Dahliana; Kharis Nugroho; Alfiyatul Azizah; Andri Nirwana, A.N. (Perkumpulan Dosen Fakultas Agama Islam Indramayu, 2024)
Religious moderation is an important concept in maintaining balance, tolerance, and harmony in a diverse society. In this context, the interpretation or interpretation of religious teachings has a very significant role. Tafsir allows for a deeper and contextual understanding of sacred texts, which in turn can support religious moderation programs. This article examines the role of tafsir in supporting religious moderation programs by focusing on several key aspects, namely: how tafsir can avoid radicalization, promote tolerance between religious communities, and strengthen national values within the framework of religious diversity. Through literature analysis and case studies, it was found that inclusive and contextual interpretation can be an effective tool in preventing extremism and promoting a harmonious life in a pluralistic society. Therefore, the involvement of interpreters in religious moderation programs is a must to ensure that the religious messages conveyed are in harmony with the values of moderation and nationality. This article concludes that interpretation plays a key role in shaping a moderate and inclusive understanding of religion, which is essential for the success of religious moderation programs.